Philoponus, Stephanus and the De Anima - Edwards, M (Brill Academic Publishers, 2023)
The Greek commentary on Aristotle’s De Anima is assigned by Michael Hayduck to Philoponus, except that he assigns Book 3 to Stephanus. The true continuation of Books 1 and 2 is now known to be a Latin text which claims to be a translation from Philoponus. Peter Lautner, however, contends that both the full commentary and the stray Book 3 are by Philoponus. Pantelis Golitsis argues that Philoponus composed the stray Book 3 while the full commentary is by his tutor Ammonius. Here it will be argued that: (a) Lautner is probably right to deny the stray Book 3 to Stephanus; (b) the criteria employed by Golitsis suggest that Philoponus had a hand in both the Greek and the Latin Book 3; (c) Philoponus is therefore likely to be the author of both the full commentary, as editor of Ammonius, and the stray Book 3 in his own right.